Detecting Heart Rate Using Pulse Sensor As Alternative Knowing Heart Condition - Yuda Irawan; Yunior Fernando; Refni Wahyuni (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2019)
Medical check-up done at the hospital for the first time is a heartbeat. This is done because the heart of the human body is the main organ, where the work function of the heart affects other important organs of humans. Based on these conditions, human heart health must be really considered. Things that can be done early is by checking the heart rate regularly. not everyone can do medical check-ups regularly. Even though by knowing the condition of a person's heartbeat, health will be maintained, it does not need expensive care from a doctor, but with a regular lifestyle, everything will be resolved. In this study, the researchers designed to measure heart rate as an alternative in maintaining health, using pulse sensors and Arduino circuits. This study resulted in a heart rate application system as a control to monitor the condition of the patient's heart rate, can provide information about the heart rate that uses the pulse sensor to patients and doctors who have an application to read the heart rate that has been made.